Manual for the geotechnical design of structures to Eurocode 7 : May 2013 (Institution of Structural Engineers, 2013)
This Manual has been published by the Institution of Structural Engineers to provide information for the design of a range of geotechnical works. The Manual, in its component parts (BS EN 1997-1 and BS EN 1997-2, along with their associated national annexes) presents designers with a unified design approach to geotechnical engineering. It provides guidance across a range of activities, from traditional foundation design to slope stability, retaining wall design, investigation and reporting. --